Presenting symptoms of cancer and stage at diagnosis: evidence from a cross-sectional, population-based study. Issue 1 (January 2020) - Koo, Minjoung Monica; Swann, Ruth; McPhail, Sean; Abel, Gary A; Elliss-Brookes, Lucy; Rubin, Greg P; Lyratzopoulos, Georgios
Summary: Background: Early diagnosis interventions such as symptom awareness campaigns increasingly form part of global cancer control strategies. However, these strategies will have little impact in improving cancer outcomes if the targeted symptoms represent advanced stage of disease. Therefore, we aimed to examine associations between common presenting symptoms of cancer and stage at diagnosis. Methods: In this cross-sectional study, we analysed population-level data from the English National Cancer Diagnosis Audit 2014 for patients aged 25 years and older with one of 12 types of solid tumours (bladder, breast, colon, endometrial, laryngeal, lung, melanoma, oral or oropharyngeal, ovarian, prostate, rectal, and renal cancer). We considered 20 common presenting symptoms and examined their associations with stage at diagnosis (TNM stage IV vs stage I–III) using logistic regression. For each symptom, we estimated these associations when reported as a single presenting symptom and when reported together with other symptoms. Findings: We analysed data for 7997 patients. The proportion of patients diagnosed with stage IV cancer varied substantially by presenting symptom, from 1% (95% CI 1–3; eight of 584 patients) for abnormal mole to 80% (71–87; 84 of 105 patients) for neck lump. Three of the examined symptoms (neck lump, chest pain, and back pain) were consistently associated with increased odds of stage IV cancer, whether reported alone or with other symptoms, whereas the opposite was true for abnormal mole, breast lump, postmenopausal bleeding, and rectal bleeding. For 13 of the 20 symptoms (abnormal mole, breast lump, post-menopausal bleeding, rectal bleeding, lower urinary tract symptoms, haematuria, change in bowel habit, hoarseness, fatigue, abdominal pain, lower abdominal pain, weight loss, and the "any other symptom" category), more than 50% of patients were diagnosed at stages other than stage IV; for 19 of the 20 studied symptoms (all except for neck lump), more than a third of patients were diagnosed at stages other than stage IV. Interpretation: Despite specific presenting symptoms being more strongly associated with advanced stage at diagnosis than others, for most symptoms, large proportions of patients are diagnosed at stages other than stage IV. These findings provide support for early diagnosis interventions targeting common cancer symptoms, countering concerns that they might be simply expediting the detection of advanced stage disease. Funding: UK Department of Health's Policy Research Unit in Cancer Awareness, Screening and Early Diagnosis; and Cancer Research UK.